Pengembangan Media Pembelajaran Pafe (Papan KPK FPB) pada Pembelajaran Matematika Kelas V SDN 47 Gresik - Annisa Ajeng Syamilah; Arissona Dia Indah Sari; Arya Setya Nugroho (Jurnal Pendidikan Dirgantara, 2026)
This study aims to develop a PAFE (KPK FPB BOARD) learning medium for KPK and FPB materials for fifth-grade students at SDN 47 Gresik. This research uses the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model, which focuses on the analysis, design, development, implementation, evaluation, and feasibility testing of the resulting learning media. This media was developed as an interactive tool capable of increasing learning interest, strengthening conceptual understanding, and providing a more enjoyable learning experience. The results indicate that Math Space media meets three main aspects of educational media development: validity, practicality, and effectiveness. In terms of validity, the media expert's assessment obtained a percentage of 95% and a percentage of 80.9%, respectively. Based on the average of the two results, the percentage obtained was 87.9%, making it highly valid. In terms of practicality and effectiveness, the N-gain calculation result of 0.80 is categorized as very effective, thus demonstrating that the use of the media significantly improves understanding of the KPK and FPB concepts. In terms of practicality, student responses reached 92.8%, indicating that this media is highly practical, easy to use, engaging, and supports independent learning. Overall, the PAFE (KPK FPB BOARD) learning media was deemed feasible, practical, and effective for use in mathematics learning, particularly in KPK and FPB. Furthermore, this media is flexible and can be used for both in-class and out-of-class learning.